1990
DOI: 10.1101/gad.4.9.1588
|View full text |Cite
|
Sign up to set email alerts
|

A major positive regulatory region located far upstream of the human alpha-globin gene locus.

Abstract: We have identified a remote, tissue-specific, positive regulatory element that is of major importance in determining the level of human c~-globin gene expression. Stable transformants containing this DNA segment linked to the c~ gene in mouse erythroleukemia cells expressed human c~ mRNA at levels that are indistinguishable from those seen in interspecific hybrids containing the human ot genes in their normal context on chromosome 16. Furthermore, all transgenic mice containing the c~ genes linked to this regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
214
1
5

Year Published

1997
1997
2010
2010

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 337 publications
(232 citation statements)
references
References 59 publications
7
214
1
5
Order By: Relevance
“…Lying 30-70 kb upstream of the α-globin genes, four highly conserved elements (multispecies conserved sequences, MCS-R1 to 4) corresponding to erythroid-specific DNase I hypersensitive sites (HS-48, HS-40, HS-33, HS-10, respectively) act as long-range regulatory elements of the α-like globin genes [4, reviewed in 5]. Several approaches like the analysis of interspecific hybrids [6] and stable transfectants [6,7], studies in transgenic mice [6,8] or in a humanized mouse model [9], provided evidence that the major regulatory element of this gene cluster in the human locus is MCS-R2 (which corresponds to HS-40). On their own, the other elements (MCS-R1, 3, 4) seem unable to induce substantial levels of α-globin gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…Lying 30-70 kb upstream of the α-globin genes, four highly conserved elements (multispecies conserved sequences, MCS-R1 to 4) corresponding to erythroid-specific DNase I hypersensitive sites (HS-48, HS-40, HS-33, HS-10, respectively) act as long-range regulatory elements of the α-like globin genes [4, reviewed in 5]. Several approaches like the analysis of interspecific hybrids [6] and stable transfectants [6,7], studies in transgenic mice [6,8] or in a humanized mouse model [9], provided evidence that the major regulatory element of this gene cluster in the human locus is MCS-R2 (which corresponds to HS-40). On their own, the other elements (MCS-R1, 3, 4) seem unable to induce substantial levels of α-globin gene expression.…”
Section: Introductionmentioning
confidence: 99%
“…Using QCP, we identified a site at À48 kb (Fig. 3a) that had not been detected in previous extensive surveys 14 . We confirmed that this site could be visualized with conventional assays (Fig.…”
Section: High-throughout Mapping Of Human Gene Regulatory Regionsmentioning
confidence: 71%
“…ARTICLES control elements of the HBA@ upstream regulatory domain and all major hypersensitive sites previously reported following laborious studies of this region with conventional hypersensitivity assays 14 .…”
Section: High-throughout Mapping Of Human Gene Regulatory Regionsmentioning
confidence: 99%
See 1 more Smart Citation
“…A distal major regulatory element located 60 kb upstream, called HS Ϫ40, is required for erythrocyte-specific expression of the human ␣-globin gene in transgenic mice (20). When HS Ϫ40 is added to reporter genes promoted by the proximal 5Ј flanking sequences of the human ␣-globin gene (but not including internal sequences), it enhances expression in transiently transfected erythroid cells (31,36).…”
Section: Discussionmentioning
confidence: 99%